Gendering international migration - Rustem Shamilevich Davletgildeev, Kamila Danilovna Shaibakova, (Opción, 2019)
The article looks at the development of the research on women migrants and establishes the occasions when women become more vulnerable and when special regimes are required in order to make migration easier and to avoid discrimination via comparative qualitative research methods. As a result, women have more likely become victims of gender-based violence especially if a ground for intersectionality can be found. In conclusion, women face unique problems in migrating that men might not be experienced. Stereotypes, intersectionality, the high risks of being subjected to domestic or sexual violence make them more vulnerable than men.